Recurrent horizontal transfer identifies mitochondrial positive selection in a transmissible cancer - Strakova, Andrea; Nicholls, Thomas J.; Baez-Ortega, Adrian; Ní Leathlobhair, Máire; Sampson, Alexander T.; Hughes, Katherine; Bolton, Isobelle A. G.; Gori, Kevin; Wang, Jinhong; Airikkala-Otter, Ilona; Allen, Janice L.; Allum, Karen M.; et al. (Springer Nature, 2020)
Autonomous replication and segregation of mitochondrial DNA (mtDNA) creates the potential for evolutionary conflict driven by emergence of haplotypes under positive selection for ‘selfish’ traits, such as replicative advantage. However, few cases of this phenomenon arising within natural populations have been described. Here, we survey the frequency of mtDNA horizontal transfer within the canine transmissible venereal tumour (CTVT), a contagious cancer clone that occasionally acquires mtDNA from its hosts. Remarkably, one canine mtDNA haplotype, A1d1a, has repeatedly and recently colonised CTVT cells, recurrently replacing incumbent CTVT haplotypes. An A1d1a control region polymorphism predicted to influence transcription is fixed in the products of an A1d1a recombination event and occurs somatically on other CTVT mtDNA backgrounds. We present a model whereby ‘selfish’ positive selection acting on a regulatory variant drives repeated fixation of A1d1a within CTVT cells.